Peran QRIS terhadap Pendapatan UMKM di Era Digital: Studi SWK Ketintang Surabaya: Penelitian - Jimly Sabda Maulana; Waspodo Tjipto Subroto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to innovate in order to improve efficiency and income. One innovation in non-cash payment systems is the Quick Response Code Indonesian Standard (QRIS), initiated by Bank Indonesia to facilitate digital transactions. This study aims to analyze the effect of QRIS usage on the income of MSME actors at the Ketintang Culinary Tourism Center (SWK), Surabaya. The research employed a quantitative approach with an explanatory design. The population consisted of all MSMEs at SWK Ketintang, with a total sample of 34 respondents determined using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the aid of SPSS software. The findings indicate that the use of QRIS has a positive and significant impact on the income of MSMEs. These results highlight the importance of digital literacy and the adoption of QRIS-based payment systems as strategies to support local economic growth. Furthermore, this study is expected to serve as a reference for MSME actors and policymakers to enhance the utilization of digital payment technologies as a key driver of business growth in the digital economy era.